Lecturer Strategy in Assignment Management as the Implementation of Academic Service Quality in the Covid-19 Period - Yayah Huliatunisa; Dadang Suhardan; Johar Permana; Diding Nurdin; Yohamintin Yohamintin; Suparta Rasyid; Irawati Sabban (Universitas Kristen Satya Wacana, 2022)
The formation of interaction, communication, and collaboration between lecturers and students, and or students in assignment management during the Covid-19 period requires lecturers to change their pedagogy quckly through choosing the right strategy. This study aims to present information as a measure of the success of lecturers’ strategies in managing assignments to write books with ISBN as an implementation of the quality of academic services during the Covid-19 period. This cross-sectional descriptive survey research method was conducted on 128 fifth semester students of A-D class, Elementary School Teacher Education Study Program, Muhammadiyah University of Tangerang, Academic Year 2020/2021, with 52 web-based questionnaires distributed online using the google form application, measured using 4 response point Likert data format without middle category, using 4 answer options: Strongly Agree, Agree, Disagree, and Strongly Disagree. The management of the assignments to write books with ISBN is very appropriate to do as a lecturer strategy to maximize the quality of academic services in curriculum development courses during the Covid-19 period.